Peran Artificial Intelligent (AI) dalam Mempertahankan Keunggulan Kompetitif Bisnis di Era Digital : Sebuah Kajian Literatur - Siti Muntamah; Nurhaeni Sikki (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
The rapid development of digital technology has brought significant changes in the business world, requiring companies to innovate and improve operational efficiency in order to maintain competitive advantage. One technology that plays a central role in this transformation is Artificial Intelligence (AI). This article aims to examine the role of AI in business through a comprehensive literature review, exploring the benefits, challenges, and strategies for implementing AI in facing competition in the digital era. AI makes a major contribution to improving operational efficiency through the automation of repetitive tasks (Duan et al., 2019), analyzing large amounts of data for more accurate decision making (Chui et al., 2016), and improving the personalization of customer experiences (Haenlein & Kaplan, 2019). However, the implementation of AI also faces a number of challenges, such as high investment costs, limited expertise, and ethical issues related to data privacy. Recommendations from this study include the importance of investing in workforce training, developing an AI implementation strategy that is aligned with business goals (Bughin et al., 2018), and improving data security to maintain customer trust. This study is expected to provide useful insights for academics and business practitioners in optimizing the use of AI to maintain competitive advantage amidst increasingly tight competition.